PENGARUH PEMASARAN SOSIAL DAN LINGKUNGAN BSINIS TERHADAP KEPUTUSAN PEMBELIAN LAPTOP LENOVO: PENGARUH PEMASARAN SOSIAL DAN LINGKUNGAN BSINIS - Esti Kiki Riski Sukran; Silfani Arfita Utami Arfah; Eko Marsolisdiono (LPPM AMBKENDARI, 2026)
This study aims to analyze the influence of social marketing and the business environment on Lenovo laptop purchasing decisions in Indonesia using a quantitative approach with multiple linear regression. The study population was Lenovo laptop consumers in urban areas of Indonesia, using a purposive sampling technique, resulting in 150 respondents. Primary data was collected through a questionnaire, which was tested for validity and reliability, and analyzed using SPSS version 26. The results showed the model had very high predictive power with an R-squared value of 0.937 (93.7%), meaning that social marketing (X1) and the business environment (X2) were able to explain 93.7% of the variation in purchasing decisions (Y), while the remaining 6.3% was influenced by other factors. Partially, social marketing has a significant positive effect on purchasing decisions (significance 0.001 < 0.05) through building consumer trust and a CSR image aligned with millennial/Gen Z values. The business environment also has a significant effect (significance 0.002 < 0.05) through easy service center access, competitive pricing stability, and adaptation to digital trends such as remote work post-pandemic. A simultaneous F-test yielded a significance value of 0.000 < 0.05, confirming the synergy of these two variables as key pillars of competitive strategy. These findings align with Social Marketing Theory (Kotler & Armstrong, 2019) and the PESTEL business environment theory (Crimmins, 2025). Practical implications for Lenovo include the need for consistent social campaigns while strengthening distribution networks to ensure long-term consumer loyalty in the competitive Indonesian laptop market. This research contributes to the development of consumer technology marketing literature in the VUCA digital era.